Encouraging Mothers for Routine Pediatric Dental Check-Up Through Cadres Empowerment Program - Setijanto, R. Darmawan; Rachmawati, Rita Yuana; Kandar, Hayyin Sabila; Hartono, Dwicha Rahma Nuriska; Novitananda, Agtadila; Laksono, Revian Gigih; Thalia, Audina; Dias, Dennaya Listya; Adityasari, Rachma; Sativa, Naura Athiyyah; Fauzi, Ahmad (Faculty of Dental Medicine Universitas Airlangga, 2019)
Background: Oral and dental hygiene is essential for physical health and well-being, and it can affect speech, mastication, and self-confidence. Children under five are not able to brush their teeth independently, do not have manual dexterity and psychological maturity to understand the importance of maintaining oral health. Therefore, parental role, especially maternal role, is critical in maintaining children's dental and oral health. An epidemiological study under Kalijudan Public Health Center coverage revealed that maternal parenting style significantly affected dental and oral health care in children per caries severity index using def-t. A promotional program was needed to strengthen the maternal perceived control domain to promote dental and oral health in children. The